Penerapan Bahan Ajar dan Luaran pada Proses Pembelajaran Bahasa Mandarin di Sekolah Menengah Umum Negeri - Sri Haryanti (Bina Nusantara University, 2012)
The objective of conducting Mandarin language learning process for senior high schools is to produce students who are capable and master such knowledge. The Government has set four types of basic competencies which must be possessed by students in learning Mandarin: the ability to listen, to speak, to read, and to write. In order to be able to transfer such abilities and knowledge, not only the teachers’ capability is required but also a suitable curriculum is needed to help achieving the objective of learning Mandarin language. The Government has set the basic criteria for curriculum and teaching material that must be included in every teaching books. In addition, the government has determined the types of basic competencies that must be accomplished in every teaching material given. Nevertheless, in practice, many schools do not adopt the guidelines that the government has set, resulting in disharmony between the government guidelines and the common practice. Such disharmony will certainly affect the competency of the teachers as well as the final outcome for the learning process, at the risk of not being able to accomplish the main objective. Article applied s the observation method and library research, as well as some personal experience as a trainer in improving the quality of teachers for Mandarin language.